Comparing different fatigue test methods at asphalt mastic level - Chaudhary, Mohit; Saboo, Nikhil; Gupta, Ankit (Springer Science and Business Media B.V., 2022)
Latest research is focused on predicting the fatigue behavior of asphalt mixtures through cost-effective and simple test methods on asphalt mastic level (asphalt binder + mineral fines). There are numerous fatigue test methods for asphalt binders and mastic using the dynamic shear rheometer (DSR). However, up to now, the results of the different fatigue tests on DSR have not been directly compared. Therefore, four different asphalt mastic mixes were prepared, and each was tested with the two most popular fatigue tests [linear amplitude sweep (LAS) test and time sweep (TS) test] and then compared to each other. The TS tests were performed as stress-controlled and as strain-controlled tests. All LAS and TS tests were performed with cylindrical and hyperbolic specimen shapes to identify impact of specimen shape. Different fatigue criteria were applied for evaluation to investigate the comparability of the results. Stress-controlled TS tests, strain-controlled TS tests, and LAS tests reveal different rankings of fatigue performance. However, a dissipated energy approach can combine stress-controlled and strain-controlled TS tests into one fatigue curve. The hyperbolic specimen shape can be used for TS tests and results in the same rankings. The hyperbolic specimen shape is not applicable for LAS tests. A calculation model could be derived to establish a relationship between the measured and actual stresses and strains in the necking of a hyperbolic specimen. TS tests using the dissipated energy approach appear to be the most promising mastic fatigue tests. © 2022, The Author(s).
Keywords: Aspahlt mastic; DSR; Fatigue; LAS; Time sweep